The Prevention of Brain Metastases in Non-Small Cell Lung Cancer by Prophylactic Cranial Irradiation - Witlox, Willem J. A.; Ramaekers, Bram L. T.; Zindler, Jaap D.; Eekers, Daniëlle B. P.; van Loon, Judith G. M.; Hendriks, Lizza E. L.; Dingemans, Anne-Marie C.; De Ruysscher, Dirk K. M. (Frontiers in Oncology, 2018)
Background Non-small cell lung cancer (NSCLC) patients frequently develop brain metastases (BM), even though the initial imaging with brain CT or MRI was negative. Stage III patients have the highest risk to develop BM, with an incidence of approximately 30%. BM can lead to neuro-cognitive disorders, loss of quality of life (QoL), and they are the most important factors influencing patient’s overall survival (OS). Although a radical local treatment of BM may be possible with primary radiosurgery or after resection, the prognosis often remains poor. Preventing the development of BM through prophylactic cranial irradiation (PCI) may improve the outcome of these patients. Methods Data from published randomized trials comparing PCI with non-PCI were sought using electronic database (PubMed) searching, hand searching, and by contacting experts. Trials were included if they considered a randomized comparison of PCI and non-PCI, enrolled NSCLC patients, excluded patients with recurrent or metastatic disease, and reported results on BM occurrence. Each RCT was assessed for methodological quality using the Cochrane collaboration’s tool for the assessment of risk of bias. Study estimates were pooled using a fixed effects sample-weighted meta-analysis approach to calculate an overall estimate and 95% CI. Results on PCI-related toxicity, QoL and OS were only reported descriptively. Results Seven RCTs were included in the meta-analysis. In total, 1,462 patients were analyzed, including 717 patients who received PCI and 745 patients who did not. The risk of developing BM was significantly decreased through PCI (13% reduction, RR 0.33; 95% CI 0.22-0.45). PCI-related toxicity and QoL data were limited. Acute toxicity mostly included fatigue, skin-related toxicity and nausea or vomiting. Late toxicities such as headache, dyspnea, lethargy and low grade cognitive impairments were also reported in some of the included RCTs. Results on OS were inconclusive. Conclusions The risk of developing BM was reduced in patients who received PCI compared to patients who did not. To implement PCI as the standard treatment for patients with NSCLC, the impact of PCI-related toxicity on QoL should be further investigated, as well as long-term OS. A future individual patient data (IPD) meta-analysis could produce definitive answers to this clinical